Flexible Electrodes: Rapid Pseudocapacitive Sodium‐Ion Response Induced by 2D Ultrathin Tin Monoxide Nanoarrays (Adv. Funct. Mater. 12/2017). (March 2017) - Chen, Minghua; Chao, Dongliang; Liu, Jilei; Yan, Jiaxu; Zhang, Bowei; Huang, Yizhong; Lin, Jianyi; Shen, Ze Xiang
Abstract : A flexible, binder free electrode composed of 2D ultrathin (≈2.5 nm) SnO nanoflake arrays on GF/CNTs foam is described by Minghua Chen, Jianyi Lin, Ze Xiang Shen, and co‐workers in article number 1606232. DFT calculations, quantitative capacitive analysis, ex‐situ Raman spectroscopy, and HRTEM verify the pseudocapacitive contribution to high rate Na + storage and long‐term cycle life of sodium ion batteries.